Vulnerabilidade socioambiental dos moradores do estuário do Rio Paraíba- PB frente as mudanças climáticas e variações do nível do mar - Carmo, Felipe Wielewski do (2017)
This study seeks to elucidate the perceived vulnerability of coastal individuals and communities along the Estuary of Paraiba River (EPR), as well as the perception of academic experts/decision-makers and laypeople on the susceptibility of the communities being negatively affected by climate change and sea level rise. The research starts from the premise that listening, discussing and comparing information reduces information asymmetry among actors, research institutions, control oversight and management bodies. Thus, one learns more, perceives more and makes feasible the discussion on effective public policies of adaptation to climate change and sea level rise, with the purpose of improving the adaptability and the resilience of the riverside communities and the environment, of the EPR. The climate crisis is the main contemporary environmental problem, has multiple and complex implications and has among its priority impacts coastal territories and communities. The methodological approach was a mixed method, combining the collection of qualitative and quantitative information through interviews and questionnaires, respectively. It was investigated the traditional knowledge, formal knowledge and the perception of risk on the climatic changes and their consequences for the population residing in the estuary and of the coastal zone of the state of Paraiba, through a review of the literature related to the subject, of documentary research of secondary data and the systematic observation of its dynamics. The research has shown that there is a certain consonance between the knowledge and perceptions of fishermen, lay people and specialists. Expressed, for example, in the unanimous preoccupation with an inevitable reordering of occupations in risk areas due to erosion and flood, and a more violent future due to scarce resources, consequences of climate change and mismanagement. It has also demonstrated that there are ecological, social, oceanographic and climatic relationships that are not clearly perceived by the actors heard in the research and that may represent future risks in the management of the problem.